Analysis of immunoglobulin G-binding-protein expression by invasive isolates of Streptococcus pyogenes. - Raeder, R (1995)
Invasive group A streptococcal isolates collected as part of a Centers for Disease Control and Prevention surveillance study were analyzed for expression of immunoglobulin G (IgG)-binding proteins. Two IgG-binding phenotypes of group A isolates of the M1 serotype were identified. The first group expressed a surface protein that bound all four human IgG subclasses (type IIo) and was recognized by rabbit anti-serotype M1-specific antiserum but not by normal rabbit serum. The second group expressed an IgG-binding protein that was also recognized by the anti-serotype M1 antiserum but demonstrated significant nonimmune reactivity only with human IgG3 (type IIb). Analysis of extracts of the isolates for reactivity with human IgA, fibrinogen, and albumin was also performed. The importance of the binding of human plasma proteins to pathogenic group A streptococci remains to be established.